Gesundheitsverhalten von Müttern während und nach der Schwangerschaft in der StädteRegion Aachen. - Dölker, Theresa (My University, 2014)
Ziel dieser Arbeit ist es, aufzuzeigen, ob und welche Personengruppen im Kreis Aachen trotz bestehender Versorgungsangebote während der Schwangerschaft und in der Zeit danach inadäquat betreut werden und in welchen Gesundheitsbereichen besondere Aufklärungs- und Präventionsmaßnahmen vonnöten sind. In Zusammenarbeit mit dem Gesundheitsamt der Stadt Aachen wurde zwischen September 2008 und Februar 2009 eine Umfrage an den vier Geburtskliniken des ehemaligen Kreises Aachen - Eschweiler, Simmerath, Stolberg, Würselen - durchgeführt. Mithilfe eines Fragebogens wurden u.a. Merkmale zum Gesundheitszustand und Risikoverhalten der Mütter sowie zum sozialen Umfeld erfasst. Insgesamt nahmen 627 (48,08%) Wöchnerinnen an der Studie teil. Mütter unter 20, sozial Benachteiligte, Migrantinnen und Alleinerziehende zeigten häufiger Risikoverhalten wie Alkohol- und Zigarettenkonsum, Übergewicht und restriktive Stillabsichten. Diese Frauen waren auch unzureichend in die Versorgungssysteme eingebunden. Teilnehmerinnen hingegen, die an einem Vorbereitungskurs teilgenommen hatten, wiesen seltener riskantes Gesundheitsverhalten auf. Am deutlichsten war der positive Einfluss von Vorbereitungskursen beim Rauchverhalten, der geplanten Stilldauer und der subjektiven Gesundheit der Frauen zu erkennen.

BACKGROUND: The objective of this study was to identify women in the rural district of Aachen who are not covered sufficiently through existing healthcare programmes during pregnancy and after delivery. Areas of special need for further education and prevention activities have been pointed out. METHODS: Between September 2008 and February 2009 a survey was conducted on the four obstetrical hospitals in the rural district of Aachen - Eschweiler, Simmerath, Stolberg and Würselen. It has been realized in cooperation with the health care office Aachen. A questionnaire was recording characteristics such as overall health, risk behaviour and social environment. RESULTS: A total of 627 (48,08%) postpartum women participated in the survey. Mothers younger than 20 years, socially disadvantaged women, migrants and single mothers showed more often risk behaviour such as consumption of alcohol, smoking, overweight and a restrictive intention of breastfeeding. These women were also found to be insufficiently integrated in social security systems. However, participants who had taken part in a preparatory course less frequently exhibited health risk behaviour. The positive effect of preparation classes was most prominent in women s smoking habits, intended breastfeeding duration and subjective health. CONCLUSION: Good prevention programmes which have a positive influence on state of health and health risk behaviour of (becoming) mothers do exist in the district of Aachen. However, women with a low social state, young aged mothers or migrants are likely to not utilize these programmes enough. A better networking between doctors, midwives and social workers is required to reach those women at risk. Further investigation is recommended to evaluate the concept of early aid ( Frühe Hilfen ) that was launched following our survey.
Health behaviour of mothers during pregnancy and after delivery in the district of Aachen.
Keywords: Gesundheitswesen; Gesundheitsvorsorge; Geburten; Mutter; Sozialstruktur; Risikoanalyse; Befragung; Schwangere; Gesundheitszustand; Schwangerschaft; Risikoverhalten; Alkohol; Tabak; Gesundheitsbetreuung; Prävention; Versorgungssystem; Gesundheitsversorgung; Untersuchungsergebnis